The ClassyFarm System in Tuscan Beef Cattle Farms and the Association between Animal Welfare Level and Productive Performance - Francesco Mariottini; Lorella Giuliotti; Marta Gracci; Maria Novella Benvenuti; Federica Salari; Luca Arzilli; Mina Martini; Cristina Roncoroni; Giovanni Brajon (Animals, 2022)
In 2018, the Italian Ministry of Health introduced the ClassyFarm system in order to categorize the level of risk related to animal welfare. The ClassyFarm checklist for beef cattle is divided into four areas: Areas A “Farm management and personnel”; B “Structures and equipment”; C “Animal-based measures”; and “Emergency plan and alert system”. Answers contribute to the final Animal Welfare Score (AWS) and to the score of each area. The aim of this work was to assess the animal welfare level on 10 Tuscan beef cattle farms through the ClassyFarm checklist and to examine the relationship between the level of animal welfare on final weight (FW), carcass weight (CW), weight gain (WG), and average daily gain (ADG). The AWS was divided into four classes, and the scores for each area were divided into three classes. The analysis of variance was applied, and AWS class, sex, and breeding techniques (open and closed cycle) were included in the model. The AWS class and sex had a highly significant influence on all parameters, while the breeding technique did not significantly influence any parameter. Farms classified as excellent presented a higher FW (677.9 kg) than those classified as good and insufficient, and the same trend was found for the ADG. The classes obtained in Areas A and C had a highly significant influence on all the parameters investigated. The classes obtained in Area B significantly influenced FW and WG. In conclusion, the productive response of the animals seemed to benefit from the welfare conditions.